2015
DOI: 10.5562/cca2743
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Substituted Cobalt Ferrites by Glycine-Nitrates Process

Abstract: Chromium substituted cobalt ferrites (CoFe2-xCrxO4, 0  x  2) were synthesized through solution combustion method using glycine as fuel, named glycine-nitrates process (GNP). As evidenced by X-ray diffraction data (XRD), single cubic spinel phase was formed for all CoFe2−xCrxO4 (0  x  2) series. The cubic lattice parameter (a) decreases with increasing chromium content. Room temperature 57 Fe Mössbauer spectra revealed the Fe 3+ and Cr 3+ site occupancy, the local hyperfine magnetic fields and the substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…During synthesis, the fusion process, which takes place at high temperatures, may accelerate the rate of crystal size increase of the final product. D. Gingasu et al observe the same observation [13].…”
Section: Structural Analysismentioning
confidence: 56%
“…During synthesis, the fusion process, which takes place at high temperatures, may accelerate the rate of crystal size increase of the final product. D. Gingasu et al observe the same observation [13].…”
Section: Structural Analysismentioning
confidence: 56%
“…The variations in the distribution of cations open up opportunities to modify the physical properties of cobalt ferrite by doping other cations. Several nanoparticle synthesis methods have been developed, including the coprecipitation method, sol-gel method, hydrothermal method, and glycine nitrate process (Amiri & Shokrollahi, 2013;Hajalilou et al, 2016;Gingasu et al, 2015). Among these methods, the coprecipitation method is the most effective and the simplest (Setiadi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors such as particle size, shape and porosity that are closely related to the synthesis method, have significant impact on the cobalt ferrite properties [12]. Among the chemical methods, special attention is given to coprecipitation and Pechini methods [13,14], sol-gel process [15,16], hydrothermal/solvothermal technique [1,[17][18][19], precursor method [20], combustion method and microwave-assisted combustion method [21][22][23][24], microemulsion method [7] and polyol process [25]. Das et al [17] reported a significant modification in the size of the particles and magnetic properties when adding the CTAB surfactant in the synthesis of CoFe 2 O 4 nanoparticles through the hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%